Buruh-buruh binaan Foochow Sitiwan di Singapura / Yong Choo Chiau - Yong, Choo Chiau (1991)
This study is about the Sitiwan Foochow construction workers who work in Singapore. A number of them are illegal migrant labours without permit. Nevertheless, they are able to face the difficulties with the aid from within their own group. The bond of clanship and Sitiwanist identity enable them to help each other in coping with various problems encountered in Singapore. This migration is encouraged by the push factors from Sitiwan and the pull factors in Singapore. The attitude towards migration is influenced by such factors like financial benefit, level of formal education and types of education (medium of instruction). The shortage of the manpower in Singapore labour market and the frequent of its foreign labour policy have also afford the position of foreign labourers in the country. This thesis is divided into five study as well as research techniques, problems encountered and pull factors which have encouraged the migration. Chapter III examines the working condition of the Foochow labourers with special emphasis on their working environment (such as the safety standard) and their relationship with the employers. Chapter IV describes in their social life in Singapore. Chapter V concludes the study. It outlines some policy implications and discusses the prospect of Sitiwan Foochow people’s participation in the construction sectors of Singapore.